2015
DOI: 10.1116/1.4906484
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate ToF-SIMS image analysis of polymer microarrays and protein adsorption

Abstract: The complexity of hyperspectral time of flight secondary ion mass spectrometry (ToF-SIMS) datasets makes their subsequent analysis and interpretation challenging, and is often an impasse to the identification of trends and differences within large sample-sets. The application of multivariate data analysis has become a routine method to successfully deconvolute and analyze objectively these datasets. The advent of high-resolution large area ToF-SIMS imaging capability has enlarged further the data handling chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…Such an analysis is extremely tedious to carry out as well as difficult to draw inferences from when performed manually. The total number of TOF‐SIMS spectra acquired – where each spectrum corresponds to a pixel – makes interpretation difficult, leading to the possibility that much significant information related to hundreds of mass peaks remains hidden (Hook et al ., ). It has also been observed that within a typical TOF‐SIMS spectrum, multiple peaks are generated from the same surface molecules, and their relative yields are often related.…”
Section: Introductionmentioning
confidence: 97%
“…Such an analysis is extremely tedious to carry out as well as difficult to draw inferences from when performed manually. The total number of TOF‐SIMS spectra acquired – where each spectrum corresponds to a pixel – makes interpretation difficult, leading to the possibility that much significant information related to hundreds of mass peaks remains hidden (Hook et al ., ). It has also been observed that within a typical TOF‐SIMS spectrum, multiple peaks are generated from the same surface molecules, and their relative yields are often related.…”
Section: Introductionmentioning
confidence: 97%
“…Time of flight secondary ion mass spectrometry (ToF-SIMS) is an analytically sensitive, information-rich surface analytical technique that has been used to investigate various biological samples, from the distribution of proteins and lipids in brain tissue [32] to high throughput screening of polymer microarrays as cell substrates [3335]. Recently, ToF-SIMS was utilized to identify differences in cell-secreted matrices [36], to confirm adsorption of complex extracellular matrix coatings [37] and to analyse variances in the surface composition of decellularized tissues from different origins [38, 39].…”
Section: Introductionmentioning
confidence: 99%
“…Automated surface analysis of large sample sets has been achieved for water contact angle measurements, X‐ray photoelectron spectroscopy, atomic force microscopy, surface plasmon resonance and time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) . ToF‐SIMS has been widely used for studying polymeric systems, and when coupled with multivariate analysis has proven to be particularly useful for establishing correlations between the surface chemistries of a library of materials with various properties such as water contact angle and cell attachment . Whilst these correlations eloquently demonstrate a relationship between surface chemistry and the interfacial performance of the materials, the models themselves are difficult to interpret as they typically feature an abundance of small ion fragments that are derived from multiple, if not all, materials present in a study and are thus difficult to assign to specific chemical functionalities or properties.…”
Section: Introductionmentioning
confidence: 99%